Is comorbidity related to the independence of patients with spinal cord injury? - Sarı, Aylin; Paker, Nurdan (Journal of Surgery and Medicine, 2020)
Aim: Apart from the complications of spinal cord injury, some comorbidities in patients with this injury should be considered in the long term. In this study, we aimed to identify the comorbidities in patients with chronic spinal cord injury and the relationship of these comorbidities with the patients’ level of independence. Methods: This retrospective cohort study involved 40 patients who had spinal cord injury and were admitted to an inpatient rehabilitation program at our hospital between March 2014 and January 2016. The participants were evaluated in terms of age, height, weight, body mass index, place of residence, and marital status. Their type, level, and duration of injury were also assessed. ASIA Impairment Scale (AIS), Functional Independence Scale (FIM), Functional Ambulation Scale (FAS), Spinal Cord Independence Scale (SCIM), and Cumulative Illness Rating Scale (CIRS) were used to evaluate the patients. Results: The mean age of the 40 patients with chronic spinal cord injury was 41.83 (16.87) years. Their most common comorbidities were genitourinary (62.5%), lower gastrointestinal (50%), and ophthalmological–otolaryngologic problems (42.5%). No correlation was found between the CIRS scores and the SCIM Personal Care, Respiratory and Sphincter Management, Mobility, and the total SCIM scores of the participants. (P=0.949, P=0.469, P=0.452, P=0.521, respectively). By contrast, the FIM scores were correlated with the SCIM scores of the cases (P=0.014). Conclusion: The most common long-term comorbidities in patients with spinal cord injury were genitourinary, lower gastrointestinal, and ophthalmological–otolaryngologic problems. However, these comorbidities were not directly related to the patients’ ambulation and independence levels.